Delayed onset of benign pleural effusion following concurrent chemoradiotherapy for inoperable non‐small‐cell lung cancer. Issue 2 (February 2015) - Kumar, R.; Patel, G.; Kichenadasse, G.; Sukumaran, S.; Roy, A.; Koczwara, B.; Bowden, J. J; Leung, J.; Woo, T.; Karapetis, C. S
Abstract Chronic benign pleural effusion (BPE) is a rare complication of concurrent chemoradiotherapy (CRT) for inoperable stage IIIA non‐small‐cell lung cancer (NSCLC). This report presents three cases of BPE, the workup to differentiate this benign condition from recurrence of cancer and recommends a pleural biopsy as part of the diagnostic process. These inflammatory exudates often remain indolent, and may not require drainage or surgical intervention. In the absence of clinical, radiological and pathological evidence of recurrent disease, we recommend clinicians manage these patients expectantly, using regular clinical assessment and imaging.